First principles study of structural stability, electronic structure and mechanical properties of alkali beryllium hydrides ABeH3 (A=K, Rb, Cs). (June 2015) - Santhosh, M.; Kanagaprabha, S.; Rajeswarapalanichamy, R.; Sudha priyanga, G.; Iyakutti, K.
Abstract: Ab initio calculations are performed to investigate the structural stability, electronic structure and mechanical properties of alkali beryllium hydrides ABeH3 (A=K, Rb, Cs) for three different crystal structures, namely orthorhombic (Pnma), monoclinic (P21 /c) and triclinic (P−1). Among the considered structures monoclinic (P21 /c) phase is found to be the most stable one for these hydrides at ambient condition. The electronic structure reveals that these hydrides are insulators. The calculated elastic constants indicate that these materials are mechanically stable at ambient condition. Graphical abstract: Highlights: Ground state properties of ABeH3 (A=K, Rb and Cs) are investigated. A structural stability is analysed under high pressure. Electronic structure reveals that these materials exhibit insulating behavior. Computed elastic moduli obey traditional mechanical stability condition. Among these materials CsBeH3 is found to be the hardest material.